Automotive informatics and communicative systems [electronic resource] : principles in vehicular networks and data exchange - Guo, Huaqun , 1967- (Information Science Reference, 2009)
"This book advances the understanding of management methods, information technology, and their joint application in business processes"--Provided by publisher.